Population Density of Asian Elephants in Huai Kha Khaeng Wildlife Sanctuary - Sukmasuang, Ronglarp (วารสารวนศาสตร์ไทย, 2022)
The population density of Asian elephants in Huai Kha Khaeng Wildlife Sanctuary was studied between 1997 and 2003, covering a period of six years. A dung-count method was used both in that area and in the area around Khao Nang Rum Wildlife Research Station (KNRWRS). Data were collected consecutively at six other study sites. Sex ratio, age structure and recruitment rate of the population were also calculated from the data gathered by both transect lines and direct observations. Results reflected that the population density around KNRWRS in both the wet and the dry seasons was 0.30 individuals/km2. In the other study sites that were located near the Huai Kha Khaeng River and had less human disturbance, there was an average density of 0.73 individuals/km2. The yearly recruitment rate of the population was between 9.31 - 11.64 %. The ratio between calf-plus-juvenile elephants to sub-adult-plus-adult elephants was 1:2.15. The sex ratio between adult males and adult females in the population was 1:6.25. This study showed acceptable results compared with other natural habitats of the animal’s distribution in the Asian region. However, elephant poaching for tusks in this area remains a major threat. The population demography, population health and genetic diversity should be investigated in the future to ensure long-term survival of the species. Keywords: population density, Asian elephant, Huai Kha Khaeng Wildlife Sanctuary